2021
DOI: 10.21203/rs.3.rs-452651/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shaping Lightwaves in Time and Frequency for Optical Fiber Communication

Abstract: In optical communications, sphere shaping is used to limit the energy of lightwaves to within a certain value over a period. This minimizes the energy required to contain information, allowing the rate of information transmission to approach the theoretical limit if the transmission medium is linear. In optical fiber, however, the sphere shaping induces Kerr nonlinearity in a peculiar way that makes analysis of transmission performance difficult, potentially lowering the communications capacity. In this articl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…B-ESS modifies the ESS algorithm such that shaped channel inputs with limited energy variations are generated. Transmitted signals with high energy variations generate a larger nonlinear interference during propagation over fiber [17], [18]. Consequently, we demonstrated that B-ESS provides significant SNR gains over ESS and K-ESS, and up to 10% rate increase.…”
Section: Introductionmentioning
confidence: 77%
“…B-ESS modifies the ESS algorithm such that shaped channel inputs with limited energy variations are generated. Transmitted signals with high energy variations generate a larger nonlinear interference during propagation over fiber [17], [18]. Consequently, we demonstrated that B-ESS provides significant SNR gains over ESS and K-ESS, and up to 10% rate increase.…”
Section: Introductionmentioning
confidence: 77%
“…For instance, it has been shown that the amount of nonlinear interference generated by a propagating signal depends not only on its average power (second-order moment), but also on its fourth-order moment (when symbols are i.i.d.) [23], [33]- [35] or, more in general, on the variations of the instantaneous power over a finite temporal window [19], [21], [36]. In this case, the use of a shorter block length N is expected to be beneficial, as it introduces a constraint on the energy of each block of N symbols.…”
Section: Probabilistic Amplitude Shapingmentioning
confidence: 99%
“…The nonlinear interference due to DM was analyzed in [19] for the CCDM, while the kurtosis-limited sphere shaping, which selects the sequences with minimum energy and low kurtosis, showed superior performance in the nonlinear regime with respect to equivalent-length ESS in a single-span scenario but not for a multi-span link [20]. Furthermore, it was shown that the nonlinear shaping gain improves by properly packing shaped sequences in time and frequency [21].…”
mentioning
confidence: 99%
“…For instance, it has been shown that the amount of nonlinear interference generated by a propagating signal depends not only on its average power (second-order moment), but also on its fourth-order moment (when symbols are i.i.d.) [22], [32]- [34] or, more in general, on the variations of the instantaneous power over a finite temporal window [18], [20], [35]. In this case, the use of a shorter block length N is expected to be beneficial, as it introduces a constraint on the energy of each block of N symbols.…”
Section: Probabilistic Amplitude Shapingmentioning
confidence: 99%
“…The nonlinear interference due to DM was analyzed in [18] for the CCDM, while the kurtosis-limited sphere shaping, which selects the sequences with minimum energy and low kurtosis, showed superior performance in the nonlinear regime with respect to equivalent-length ESS in a single-span scenario but not for a multi-span link [19]. Furthermore, it was shown that the nonlinear shaping gain improves by properly packing shaped sequences in time and frequency [20].…”
mentioning
confidence: 99%